2008
DOI: 10.1016/j.bbmt.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Change as a Predictor of Outcome among Patients with Classic Chronic Graft-versus-Host Disease

Abstract: We analyzed outcomes for 668 patients who had systemic treatment for chronic graft-versus-host disease (GVHD) to assess the utility of early treatment change for exacerbation of chronic GVHD as a surrogate for survival endpoints in clinical trials. Fifty-six percent of patients had treatment change within 2 years after diagnosis of chronic GVHD. The median onset of treatment change was 4.4 months (range, 0.3 – 50 months). The cumulative incidence of non-relapse mortality (NRM) at 2 years was 16%, and overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 13 publications
3
29
0
1
Order By: Relevance
“…9,10 We also demonstrated that addition of a new treatment was associated with higher non-relapse and overall mortality, which is in agreement with previous studies. 15,16 Inamoto et al published two analyses of FFS in patients who received first-line 9 or second-line 10 therapy for chronic GVHD at a single institution. The median duration of FFS and the rates of FFS at 6 months and 2 years in the current study are similar to their results 9,10 despite the differences in cohort definition.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 We also demonstrated that addition of a new treatment was associated with higher non-relapse and overall mortality, which is in agreement with previous studies. 15,16 Inamoto et al published two analyses of FFS in patients who received first-line 9 or second-line 10 therapy for chronic GVHD at a single institution. The median duration of FFS and the rates of FFS at 6 months and 2 years in the current study are similar to their results 9,10 despite the differences in cohort definition.…”
Section: Discussionmentioning
confidence: 99%
“…59 Thalidomide has diverse immune-modulating effects including: (1) reduced levels of TNF-a; (2) co-stimulation of T cells to produce IL-2 and IFN-g; (3) inhibition of other cytokines like IL-1b, IL-6, IL-12; (4) downregulation of cell surface adhesion molecules involved in leukocyte migration; and (5) anti-angiogenesis. 48,57,60 Its biological activities are contrasted with other IMiDs in Figure 1. There are seven phase-2 and three phase-3 trials of thalidomide in cGVHD.…”
Section: Imid-class Drugsmentioning
confidence: 99%
“…An effort to decrease corticosteroid doses has led to their use in combination with other immunosuppressants, such as cyclosporine, tacrolimus, and sirolimus, in frontline or second-line settings, despite a lack of clinical evidence supporting additional efficacy after combining these agents with corticosteroids. [7][8][9][10][11][12] Patients who have persistent cGVHD after frontline therapy and require a change in treatment have a 2.5 times increased risk of nonrelapse mortality 13 ; however, there is no standard of care or approved second-line treatment.…”
Section: Introductionmentioning
confidence: 99%